AB0749 Impact of Patient Perception of Psoriasis and Psoriatic Arthritis Severity on Patient-Reported Outcomes: An Analysis from The Adelphi Database. (15th July 2016) - Boehncke, W.-H.; Piercy, J.; Chen, S.; Hojnik, M.; Ganz, F.
Abstract : Background: Patients (pts) with psoriatic arthritis (PsA) report experiencing different levels of skin involvement (psoriasis, PsO). The impact of pt perception of PsO and PsA severity on pt-reported outcomes (PROs) in PsA pts is not clearly understood. Objectives: To examine the impact of perception of PsO and PsA severity (assessed by self-completion questionnaires) in PsA pts on PROs in real world setting. Methods: This retrospective analysis extracted data from the Adelphi 2014 Rheumatology disease-specific programme (DSP). 1 The DSP is a large multi-center, multi-country, cross-sectional survey of pts with a physician confirmed diagnosis of PsA. Pts filled out a self-completion form providing an assessment of their symptoms, satisfaction with disease control and quality of life. Pts reported their perception of PsA severity as mild, moderate or severe, both at diagnosis and at the time of survey. Pts reported their perception of PsO severity on a numeric rating scale of 0–10 (0, No PsO; 1–3, Mild; 4–7, Moderate; 8–10, Severe) only at the time of survey. The self-assessment questionnaires also included Dermatology Quality of Life (DLQI), alternative Health Assessment Questionnaire – Disability Index (HAQ-DI), Work Productivity and Activity Impairment (WPAI), and Euro Quality of Life 5 Dimensions (EQ5D). Pts with PsA diagnosis were stratified by self-reported severity of both PsA and PsO. Statistical differences between the groups were evaluated using χ 2 test (categorical variables) or analysis of variance (ANOVA, continuous variables). Results: Of the 329 PsA pts analyzed from the Adelphi database, similar number of pts reported either mild (164, 50%) or moderate-to-severe PsA (165, 50%) symptoms, at the time of survey (Table 1 a). At the time of PsA diagnosis, majority of pts (292, 88%) reported experiencing moderate-to-severe PsA symptoms. At the time of survey, greater number of pts reported mild-to-moderate PsO (223, 68%) and the remaining pts reported no PsO (69, 21%) or severe PsO (37, 11%) symptoms. There was a significant association between the perception of PsA and PsO severity at the time of survey (P<0.001). The frequency and severity of itching increased significantly with increasing perception of PsO and PsA severity (P<0.001, Table 1 b). However, the severity of itching was much more pronounced in pts with severe PsO. DLQI and WPAI scores were significantly impacted by increasing severity of both PsA and PsO (P<0.001). The HAQ-DI and EQ5D scores were significantly influenced by severity of both PsA (P<0.001 for HAQ-DI and EQ5D) and PsO (HAQ-DI: P<0.05; EQ5D: P<0.01); however, a larger effect on HAQ-DI and EQ-5D scores were observed in pts with severe PsA. Conclusions: Pt perception of PsO severity mostly impacted the frequency and severity of itching, DLQI, and WPAI measures, while pt perception of PsA severity at survey negatively influenced all pt reported outcome (PRO) measures. References: Anderson et al., Curr Med Res Opin., 2008; 24 (11):3063–72. Acknowledgement: AbbVie participated in the analysis and interpretation of the data, and in writing, review, and approval of the publication. Medical writing support was provided by Deepa Venkitaramani, PhD, of AbbVie. Disclosure of Interest: W.-H. Boehncke Grant/research support from: Abbvie, Biogen Idec, Celgene, Covagen, Galderma, Janssen, Leo, Lilly, MSD, Novartis, Pantec Biosolutions, Pfizer, and UCB, Consultant for: Abbvie, Biogen Idec, Celgene, Covagen, Galderma, Janssen, Leo, Lilly, MSD, Novartis, Pantec Biosolutions, Pfizer, and UCB, Speakers bureau: Abbvie, Biogen Idec, Celgene, Covagen, Galderma, Janssen, Leo, Lilly, MSD, Novartis, Pantec Biosolutions, Pfizer, and UCB, J. Piercy Employee of: Adelphi Real World, S. Chen Shareholder of: AbbVie, Employee of: AbbVie, M. Hojnik Shareholder of: AbbVie, Employee of: AbbVie, F. Ganz Shareholder of: AbbVie, Employee of: AbbVie